Voluntary Brain Waste and the Reservation Wage of Migrants. Evidence from Austria and Three CEE Countries - Klaus Nowotny (European Regional Science Association (ERSA), 2012)
Stylized facts show that migrants more often face overqualified employment than natives. As shown by previous research, one third of the employed foreign born with tertiary education in the EU-15 are overqualified, with levels reaching up to 57.6%, compared to 20.9% among natives. Among the employed foreign born with medium education levels (ISCED 3-4), about one fifth (19.8%) is overqualified in the EU-15, compared to 7.4% of the natives. For the U.S., research shows that among employed migrants with tertiary education who immigrated in the 1990s only 21-76% obtained skilled jobs, depending on the country of origin. Whether this 'brain waste' is 'involuntary', e.g., the result of labor market discrimination or due to limited transferability of qualifications, or 'voluntary' is, however, unresolved; migrants may be willing to accept a job-skill-mismatch as long as they receive a compensation for working in overqualified employment. This paper therefore analyzes the impact of the willingness to accept overqualified employment on the reservation wage of prospective medium and highly skilled migrants. The empirical analysis uses individual level data surveyed in 2010 in Austria, the Czech Republic, Slovakia and Hungary. The survey was designed to identify migration and cross-border commuting intentions in these four countries and is especially suited to the analysis in this paper because it avoids the selection problems which would be associated with estimating migrants' reservation wages after migration. The theoretical and empirical models in this paper show that overqualified employment is not necessarily the outcome of labor market discrimination of migrants in the host country, but can also represent the migrant's rational choice as long as she is compensated for the disutility of the job-skill mismatch by a higher wage: according to the empirical estimates the compensation required for accepting overqualified employment abroad is about 11% of the income the individual could earn at home. Furthermore, the relative reservation wage increases with age. A higher income at home on the other hand decreases the relative reservation wage, but the income variable is only significant at the 10% level. The estimated parameters of the country fixed effects show that even after controlling for individual characteristics the relative reservation wage in the CEECs considered (the Czech Republic, Slovakia and Hungary) is considerably higher than in Austria: according to the regression results, potential migrants from the CEE countries require a relative reservation wage that is 100-150% higher than those of prospective Austrian migrants.
Keywords: 15; J24; J31; F22; C24; 330; brain waste; overqualification; migration; reservation wage; interval regression